2006
DOI: 10.1126/science.1123769
|View full text |Cite
|
Sign up to set email alerts
|

A Bifurcating Pathway Directs Abscisic Acid Effects on Stomatal Closure and Opening in Arabidopsis

Abstract: Terrestrial plants lose water primarily through stomata, pores on the leaves. The hormone abscisic acid (ABA) decreases water loss by regulating opening and closing of stomata. Here, we show that phospholipase Dalpha1 (PLDalpha1) mediates the ABA effects on stomata through interaction with a protein phosphatase 2C (PP2C) and a heterotrimeric GTP-binding protein (G protein) in Arabidopsis. PLDalpha1-produced phosphatidic acid (PA) binds to the ABI1 PP2C to signal ABA-promoted stomatal closure, whereas PLDalpha1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

11
333
1
2

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 361 publications
(352 citation statements)
references
References 23 publications
11
333
1
2
Order By: Relevance
“…The results further suggest that PLDa1 is not needed for ABA-induced stomatal closing when ABI1 is deleted. These findings are interesting in light of these and other recent findings that several PP2Cs function as negative regulators of ABA signaling (Leonhardt et al, 2004;Saez et al, 2004;Kuhn et al, 2006;Yoshida et al, 2006), but deletion of the ABI1 PP2C is sufficient to restore PLDa1-independent ABAinduced stomatal closing in plda1 (Mishra et al, 2006). Finally, we show here that the abi1-2 and abi1-3 knockout lines show enhanced ABA-induced stomatal closing.…”
Section: Discussionsupporting
confidence: 55%
See 2 more Smart Citations
“…The results further suggest that PLDa1 is not needed for ABA-induced stomatal closing when ABI1 is deleted. These findings are interesting in light of these and other recent findings that several PP2Cs function as negative regulators of ABA signaling (Leonhardt et al, 2004;Saez et al, 2004;Kuhn et al, 2006;Yoshida et al, 2006), but deletion of the ABI1 PP2C is sufficient to restore PLDa1-independent ABAinduced stomatal closing in plda1 (Mishra et al, 2006). Finally, we show here that the abi1-2 and abi1-3 knockout lines show enhanced ABA-induced stomatal closing.…”
Section: Discussionsupporting
confidence: 55%
“…A major advance in the study of ABA effect on stomatal closure and opening has been recently reported by Mishra et al (2006). This work shows that ABA signaling bifurcates at ABI1 and the heterotrimeric G-protein a-subunit GPA1 to regulate ABAmediated stomatal closure and inhibition of stomatal opening.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…GPA1 transcripts are present in guard cells (Wang et al 2001), and studies using Arabidopsis knockout mutants have shown that GPA1 mediates ABA inhibition of inward K + channels and stomatal opening, but not stomatal closure (Wang et al 2001;Mishra et al 2006). The specific expression of both AGB1 and AGG2 in guard cells suggests that they may function in stomatal regulation together with GPA1.…”
Section: Discussionmentioning
confidence: 99%
“…7). PA may stimulate root growth by mediating signal transduction, membrane trafficking, and/or cytoskeletal rearrangements (Anthony et al, 2004;Mishra et al, 2006;Wang et al, 2006). The binding of PA to phosphoinositidedependent protein kinase 1 is involved in root growth (Anthony et al, 2004).…”
Section: Discussionmentioning
confidence: 99%